2015
DOI: 10.1016/j.crvi.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract of mycelia from Phytophthora infestans-induced resistance in potato

Abstract: Plants recognize certain microbial compounds as elicitors in their active defence mechanisms. It has been shown that a series of defence reactions are induced in potato plant cells after treatment with water-soluble hyphal wall components prepared from Phytophthora infestans. In this study, a methanol extract from mycelia of P. infestans (MEM), which contains lipophilic compounds, was used as another elicitor for the induction of the defence reactions in potato. MEM elicitor induced reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Some examples may be the B. cinerea-secreted cerato-platanin BcSpl1 that induces systemic resistance in tobacco against two plant pathogens, Pseudomonas syringae and B. cinerea (Frías et al 2011(Frías et al , 2013; the protein VdCP1 secreted by Verticillium dahliae during host infection, being able to confer resistance against B. cinerea and Pseudomonas syringae pv. tabaci in tobacco and to V. dahliae in cotton (Zhang et al 2017); the fungal elicitor protein PebC1 from B. cinerea which improves disease resistance in A. thaliana (Zhang et al 2014) and the methanol extract of mycelium of Phytophthora infestans that induces resistance in potato plants against Phytophthora infestans (Monjil et al 2015).…”
Section: Fungal Extracts Are Potential Candidates For the Formulation...mentioning
confidence: 99%
“…Some examples may be the B. cinerea-secreted cerato-platanin BcSpl1 that induces systemic resistance in tobacco against two plant pathogens, Pseudomonas syringae and B. cinerea (Frías et al 2011(Frías et al , 2013; the protein VdCP1 secreted by Verticillium dahliae during host infection, being able to confer resistance against B. cinerea and Pseudomonas syringae pv. tabaci in tobacco and to V. dahliae in cotton (Zhang et al 2017); the fungal elicitor protein PebC1 from B. cinerea which improves disease resistance in A. thaliana (Zhang et al 2014) and the methanol extract of mycelium of Phytophthora infestans that induces resistance in potato plants against Phytophthora infestans (Monjil et al 2015).…”
Section: Fungal Extracts Are Potential Candidates For the Formulation...mentioning
confidence: 99%
“…Previously, we have reported that crude elicitor derived from the mycelia of P. infestans extracted by methanol (Pi-MEM) can induce the resistance reactions in potato (Monjil et al, 2015). Treatment with Pi-MEM can induce the ROS production in potato suspension cells and leaves, and production of sesquiterpenoid phytoalexins (rishitin, lubimin and oxylubimin) in potato tubers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Monjil et al found that a synthetic bis-aryl-methanone compound (NUBS-4190) and a methanol extract from a pathogen (the mycelia of P. infestans) that contained lipophilic compounds were elicited by potato leaves in response to NO. 169,170) The gene for Arabidopsis thaliana nitric oxide-associated 1 (AtNOA1) has been identified as a putative regulator of NOS activity in plants. 171) In N. benthamiana leaves, the pathogenesis-related 1a (NbPR1a) gene and nitric oxide associated 1 (NbNOA1) gene, a homolog of AtNOA1, were found to be associated with infection resistance.…”
Section: •−mentioning
confidence: 99%